Caracterização química do óleo essencial de croton grewioides e avaliação dos seus efeitos e do anetol como suplementos de meio de cultivo in vitro de tecido ovariano bovino - Silva, Felipe Ferreira da (2023)
Assisted reproduction techniques (ART) have contributed to greater roduction in beef and dairy cattle. The in vitro culture of ovarian follicles aims to support the development of preantral follicles in vitro. However, the high levels of reactive oxygen species (ROS) causes cell death. Therefore, the use of antioxidant agents is vital for cell protection in vitro. The Croton grewioides essential oil (CGEO) and anethole have well-known antioxidant potential. Against this backdrop, the present study evaluated the effects of anethole and OECG on activation, growth, follicle survival and stromal cell density and collagen content in bovine ovarian tissue. The activity of the enzymes superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), the thiol concentration and mRNA levels for SOD, CAT, GPX1, peroxiredoxin 6 (PRDX6) and nuclear factor erythroid 2-related factor 2 (NRF2) were also measured. For this purpose, ovarian cortex fragments (3x3x1 mm) from 16 cows were fixed in 10% paraformaldehyde (uncultured control) or cultured in vitro in 500 µL of control medium alone or supplemented with anethole or CGEO at concentrations of 1, 10, 100 or 1000 µg/mL, at 38.5°C with 5% CO2 in air for 6 days. The control medium was α-MEM containing BSA, glutamine, penicillin/streptomycin, hypoxanthine, insulin, selenium and transferrin (α-MEM+). At the end of culture, the tissues were fixed and processed for classical histology. The follicles were classified as primordial or developing, as well as morphologically normal or degenerated. Ovarian stromal cell density and collagen content were analysed separately in 10 areas of 100 µm2 for each treatment. Enzymes activity, thiol and mRNA levels were measured in tissues cultured in α-MEM+ alone or with 1 µg/mL of anethole or CGEO. The rates of primordial follicles, follicle development or follicle survival were analysed using the Chi-squared test. Cell density, enzyme activity and mRNA expression data were analysed by Kruskal-Wallis test. Tissues cultured in the presence of 1 µg/mL anethole or CGEO had significantly higher levels of morphologically healthy follicles than those in α-MEM+. Also, tissues cultured with 1 µg/mL CGEO showed higher cell density and collagen content when compared to the uncultured control. Ovarian tissues cultured in CGEO showed significantly higher thiol levels than the other groups. Anethole increased CAT activity, while OECG increased GPX activity when compared to α-MEM+. The use of anethole or CGEO reduced mRNA levels for CAT, PRDX6 and NRF2 when compared to α-MEM+. CGEO reduced mRNA levels for GPX1 when compared to α-MEM+. In conclusion, 1 µg/mL of anethole or CGEO promotes follicle survival and regulates thiollevels, mRNA expression and antioxidant enzymes activity in bovine ovarian tissue cultured in vitro.